Lessons learned from GSR projects in the colombian Pacific Region - Valencia Chávez, Daniela; Serrano Guzmán, Maria Fernanda; Pérez Ruiz, Diego Darío (Ingeniería Solidaria, 2025)
Introduction: Formulation of best practices for the execution of projects funded by the General Royalties System (SGR) in Colombia’s Pacific Region (2012–2022), conducted at Pontificia Universidad Javeriana Cali in 2023. Problem: The SGR has funded over 24,000 projects in the Pacific Region of Colombia, but improvements in quality of life have been limited. This situation is exacerbated by structural issues such as corruption, insecurity, and deficiencies in project management. Objective: The study identifies and systematizes best practices in SGR-funded projects, analyzing both successful and critical cases (2012–2022). Methodology: A total of 3,864 SGR projects (2012–2022) were analyzed. A representative sample of fully completed projects was selected, and performance indicators and risk management practices were systematically assessed using data from multiple sources. Results: Successful projects were characterized by efficient planning, risk management, and continuous supervision. In contrast, underperforming projects faced recurrent issues in planning, corruption, and low citizen participation. Conclusion: Context-specific risk management, combined with realistic and participatory planning, significantly enhances the efficiency of public investment and its impact on communities. Originality: This research fills a gap in the literature on territorial public management by offering a typology of evidence-based good practices from a historically disadvantaged region. Limitations: Findings are limited to the Pacific Region and projects with complete data, requiring additional studies for broader generalization.
Keywords: public investment; project evaluation; risk; public administration; regional development